An Approach Based on Chain Key Predistribution against Sybil Attack in Wireless Sensor Networks. (10th November 2013) - Cheng, Chunling; Qian, Yaqiu; Zhang, Dengyin
Abstract : In wireless sensor networks (WSN), Sybil attack can destroy the routing and data distributed storage mechanisms through fabricating identity information of legitimate nodes. This paper presents a chain key predistribution based approach against Sybil attack. To enhance the security of common keys between neighboring nodes, during the chain key predistribution phase, our approach uses a lightweight hash function to generate several chain keys by hashing the unique identity information of every node sequentially in the trusted base station. These chain keys construct a pool of chain keys. During the pairwise key authentication establishment phase, a node-to-node chain key based authentication and exchange (CK-AE) protocol is proposed, by which each node can share the unique pairwise key with its neighboring node. The CK-AE protocol is provably secure in the universally composable security model (UCSM). Finally, we analyze our approach from the resilience of network and the performance overhead, and the results show that our approach can not only enhance the ability of resilience to Sybil attack, but also reduce the communication overhead significantly at the cost of a certain amount of computational overhead.